Identification of human activity pattern in controlled web environment: an adaptive framework. (9th October 2019) - Chakraborty, Ayan; Banerjee, Debdeep; Goswami, Radha Tamal
This paper projects a new aspect regarding the research works based on human web based activity pattern analysis. Web activity pattern analyser is basically a part of the main goal of the research, human psycho emotional behavioural pattern analysis. In the recent era, human world is majorly dependant on internet in their life for various aspects and that is why internet usage pattern of each individual user is growing as a very powerful resource to know him. The need of web users can be mitigated more efficiently if their requirements are known to the providers. These usage patterns are found to be unique for each user, to some extent, as per the current psycho emotional state of that individual user when he or she is in a controlled web environment and this can be another mark of authentication of that particular user. This concept has already been applied in some real world application domains namely; user authentication protocol, personalised e-learning and link data analysis for resource description framework in semantic web.